Multi-gene measurable residual disease assessed by digital polymerase chain reaction has clinical and biological utility in acute myeloid leukemia patients receiving venetoclax/azacitidine - Amanda C. Winters; Mohd Minhajuddin; Brett M. Stevens; Ajay Major; Grace Bosma; Diana Abbott; Nicholas Miltgen; Ji Yuan; Amy L. Treece; Bradford J. Siegele; Mark D. Ewalt; Jonathan A. Gutman; et al. (Haematologica, 2023)
Venetoclax with azacitidine (ven/aza) is a lower-intensity therapeutic regimen that has been shown to improve outcomes in elderly patients with acute myeloid leukemia (AML). Measurable residual disease (MRD) using flow cytometry is a valuable tool for the prediction of relapse in AML using conventional therapies and ven/aza; however, the prognostic value for broadscale molecular MRD after ven/aza treatment is less clear. We aimed to determine the utility of retrospective assessment using multi-gene molecular MRD by droplet digital polymerase chain reaction (ddPCR). We found this approach correlates with outcomes in a cohort of patients receiving frontline ven/aza for AML. The predictive value of ddPCR MRD persisted when NPM1 mutations were removed from analysis, as well as after adjustment for the impact of stem cell transplant on outcomes. Late achievement of MRD negativity, including after SCT, was still associated with superior outcomes compared to persistently detectable MRD. We further explored the impact of ven/aza on the burden of different classes of mutations, and identified the persistence of splicing factor mutations, commonly associated with MDS, as a consistent finding after ven/aza treatment. These data add to our understanding of the effects of ven/aza on AML disease biology and provide details on molecular depth of remission that can guide prospective trials in the future.